CLIMATE FINANCE TOWARDS GREENER AGRICULTURE: A WIN-WIN STRATEGY - Michelle Márcia Viana Martins; Scarlett Queen Almeida Bispo; Fernanda Aparecida Silva; Heloisa Lee Burnquist; Angel Manuel Benitez Rodriguez (Revista Tempo do Mundo)
International agreements, like the Paris Agreement, obligate developed countries to financially support developing countries (DCs) in mitigating greenhouse gas (GHG) emissions and adapting to climate change. However, these investments have fallen short, mainly to sustainable agricultural projects, requiring a smart solution. Countries with vast agricultural production and forest reserves, like Brazil and Indonesia, are major contributors to GHG emissions through deforestation. The objective of this study is to assess the role of climate finance in assisting DCs in mitigating GHG emissions and adapting to climate change, particularly in the agricultural sector. The methodology adopted includes a policy-oriented approach, proposing the establishment of the Sustain (Sustainable Financing in Specific Territories for Reforestation, Recovering and Nature) mechanism. We recommend strengthening the management of climate finance to ensure that DCs achieve ambitious goals for reducing GHG and adapting to climate change with a mechanism Sustain. As a first step, the Group of Twenty (G20) should establish the Sustain as a financing modality within the climate fund aimed at addressing issues related to agriculture and land use change. Sustain will serve as an international platform to attract foreign investment for ecosystem preservation and food supply in DCs. Key recommendations for project selection include: prioritizing DCs involved in international trade and committed to sustainable production; supporting projects that promote low-carbon agricultural practices; developing standardized monitoring and reporting procedures for GHG emissions reductions; encouraging the adoption of international agricultural sustainability standards; and ensuring social inclusion and gender equity in the project benefits. The G20 should co-finance these projects by combining its resources with other investments.